2019
DOI: 10.1111/cas.14007
|View full text |Cite
|
Sign up to set email alerts
|

Serum deprivation‐response protein regulates aldehyde dehydrogenase 1 through integrin‐linked kinase signaling in endometrioid carcinoma cells

Abstract: Endometrioid carcinoma ( EC ) is one of the most common malignancies of the female genital system. We reported previously that aldehyde dehydrogenase 1 ( ALDH 1), a predominant isoform of the ALDH family in mammals and a potential marker of normal and malignant stem cells, is related to the tumorigenic potential of EC . We compared the levels of various proteins in human EC cells with high and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…CRISPR technology was used to show that serum deprivation-response protein affects the expression of ALDH1 in HEC1B, HEC-108, HEC-116, and SNG-M cells. These studies essentially represent endometrioid carcinomas [118]. In serous carcinoma cell lines, CRISPR technology was used to introduce mutations in FBXW7 , F-box, and WD repeat domain containing 7.…”
Section: Model Systemsmentioning
confidence: 99%
“…CRISPR technology was used to show that serum deprivation-response protein affects the expression of ALDH1 in HEC1B, HEC-108, HEC-116, and SNG-M cells. These studies essentially represent endometrioid carcinomas [118]. In serous carcinoma cell lines, CRISPR technology was used to introduce mutations in FBXW7 , F-box, and WD repeat domain containing 7.…”
Section: Model Systemsmentioning
confidence: 99%
“…We found that NNMT is related to MELF pattern invasion of EC and that depletion of NNMT markedly attenuates the migration and invasion of EC cells. Previously, we reported that high S100A4 and SDPR expression in EC are related to MELF pattern invasion and showed the genetic characteristics of EC with MELF invasion 3,4 . However, we did not explore what contributed to the characteristic morphology in invasive front area of MELF.…”
Section: Discussionmentioning
confidence: 85%
“…Pathological changes in these genes can cause anomalistic transduction of signal pathways such as AKT‐/‐PI3K, NF‐κB, MARK, and Wnt‐/‐β‐catenin, or abnormal expression of P53 and P16 proteins, leading to uncontrolled cell proliferation and tumorigenesis. Given its extensive study in tumors and obvious therapeutic effect, the CRISPR‐Cas9 technology has been used in related research and treatment of endometrial cancer (summarized in Table ).…”
Section: Endometrial Cancer and Crispr‐cas9mentioning
confidence: 99%
“…Knockout of S100A4 in the endometrial cancer cell line, HEC‐1B, by the CRISPR‐Cas9 technology, inhibits AKT phosphorylation and activation of MMP2, leading to reduced proliferation and invasion of HEC‐1B cells . SDPR gene depletion by CRISPR‐Cas9 in HEC‐1B and HEC‐108 cells can suppress tumor cell migration, invasion and EMT by inhibiting the ILK‐/‐ALDH1 pathway . Knockout of MIR‐203 in RUCA‐1 cells caused tumor cells to stagnate in the G2 phase of the cell cycle and cell viability also decreased .…”
Section: Endometrial Cancer and Crispr‐cas9mentioning
confidence: 99%